Association Between Hippocampus, Thalamus, and Caudate in Mild Cognitive Impairment APOEε4 Carriers: A Structural Covariance MRI Study - Novellino, Fabiana; López, María Eugenia; Vaccaro, Maria Grazia; Miguel, Yus; Delgado, María Luisa; Maestu, Fernando (Frontiers in Neurology, 2019)
Objective: Despite the Apolipoprotein E (APOE) genotype is widely recognized as one of the most important risk factors for Alzheimer’s Disease (AD) development, the neural mechanisms by which the ε4 allele promote the AD occurring remain under debate. The aim of this study was to evaluate neurobiological effects of the APOE-genotype on the pattern of the structural covariance in mild cognitive impairment (MCI) subjects. Methods: We enrolled 95 MCI subjects and 49 healthy controls. According to APOE-genotype, MCI subjects were divided into 3 groups: APOEε4 non-carriers (MCIε4-/-, n=55), APOEε4 heterozygous carriers (MCIε4+/-, n=31), and APOEε4 homozygous carriers (MCIε4+/+, n=9) while all controls were APOEε4 non-carriers. In order to explore their brain structural pattern, T1-weighted anatomical brain 1.5T-MRI scans were collected. A whole brain voxel based morphometry (VBM) analysis was performed and all significant regions (p<0.05 family-wise error, whole brain) were selected as a region of interest (ROI) for the structural covariance analysis. Moreover, in order to evaluate the progression of the disease, a clinical follow-up was performed for two years. Results: The F-test showed in VBM analysis a strong overall difference among the groups in the middle frontal and temporal gyri and in the bilateral hippocampi, thalami and parahippocampal gyri, with a grading in the atrophy in these latter three structures according to the following order: MCIε4+/+ > MCIε4+/- > MCIε4-/- > controls. Structural covariance analysis revealed a strong structural association between left thalamus and left caudate and between right hippocampus and left caudate (p<0.05 FWE, whole brain) in MCIε4 carriers groups (MCIε4+/+ > MCIε4+/-), whereas no significant associations were observed in MCIε4-/- subjects. Of note, the 38% of MCIs enrolled in this study developed AD within two years of follow-up. Conclusion: This study improves the knowledge on neurobiological effect of APOE ε4 in early pathophysiological phenomena underlying the MCI-to-AD evolution, as our results demonstrate changes in the structural association between hippocampal formation and thalamo-striatal connections occurring in MCI ε4 carriers. Our results strongly support the role of subcortical structures in MCI ε4 carriers and open a clinical window on the role of these structures as early disease markers.